2006
DOI: 10.1111/j.1601-0825.2005.01179.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical stress induces expression of cytokines in human periodontal ligament cells

Abstract: These results suggest that hPDL cells may play a role in the production of cytokines in response to mechanical stress in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
2
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 15 publications
1
47
2
2
Order By: Relevance
“…The results of the current study indicate that various fibroblastic cells naturally produce OPG, thereby supporting the inhibitory roles of fibroblasts on osteoclastogenesis. There are also significant findings showing that mechanical force induces the production of both OPG and RANKL by PLF, while OPG is predominant over RANKL [Yamamoto et al, 2006;Nakajima et al, 2008;Kook et al, 2009]. Importantly, however, the results from GCF analysis showed that the levels of RANKL are naturally higher than those of OPG in this cell type.…”
Section: Discussionmentioning
confidence: 68%
“…The results of the current study indicate that various fibroblastic cells naturally produce OPG, thereby supporting the inhibitory roles of fibroblasts on osteoclastogenesis. There are also significant findings showing that mechanical force induces the production of both OPG and RANKL by PLF, while OPG is predominant over RANKL [Yamamoto et al, 2006;Nakajima et al, 2008;Kook et al, 2009]. Importantly, however, the results from GCF analysis showed that the levels of RANKL are naturally higher than those of OPG in this cell type.…”
Section: Discussionmentioning
confidence: 68%
“…In addition, clinical studies have demonstrated that levels of cytokines, such as interleukin (IL) 1β, IL8, and cyclooxygenase (COX) 2, are increased in gingival crevicular fluid in orthodontic patients during active therapy [25]. Although the enhanced production of proinflammatory cytokines may indeed be due to the additional plaque accumulation caused by orthodontic appliances, a number of invitro studies point to the fact that these molecules can also be upregulated by biomechanical forces [28,32]. Therefore, orthodontic forces in combination with occlusal forces could accelerate periodontal destruction by the enhancement of periodontal inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Interleukin (IL) 1β, IL8 und Zyklooxygenase (COX) 2 in der gingivalen Sulkusflüssigkeit bei kieferorthopädischen Patienten wäh-rend der aktiven Therapie erhöht ist [25]. Obwohl die verstärkte Synthese proinflammatorischer Zytokine tatsächlich die Folge einer verstärkten Plaqueakkumulation durch kieferorthopädische Geräte sein könnte, so deuten doch zahlreiche In-vitro-Studien darauf hin, dass die Synthese von Entzündungsmolekülen auch durch biomechanische Kräfte induziert werden kann [28,32]. Somit könnten kieferorthopädische Kräfte in Verbindung mit okklusalen Belastungen den Abbau des Parodonts durch eine Verstärkung der parodontalen Entzündung beschleunigen.…”
Section: Introductionunclassified
“…Our pattern (a) is also related to interleukin 8 (IL-8). It was reported that mechanical stress induced expression of IL-8 and IL-6 in human periodontal ligament cells [10]. Mast cells may be influenced by barometric pressure and be an important source of TNFalpha and IL-6 [11].…”
Section: (A)mentioning
confidence: 99%